(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article is devoted to the study and development of prognostic criteria for the severity of acute coronary syndrome, which is of great importance for health authorities in the organization of specialized cardiology and rehabilitation services. The proposed method allows early diagnosis and prevention of myocardial infarction, which is of great practical importance.